Technology to Improve the Assessment of Learning. - Raposo-Rivas, Manuela; Cebrián-de-la-Serna, Manuel (Universitat de Barcelona, 2019)
The methodologies of assessment are one of the indicators of quality in teaching, to the point that the idea "tell me how you evaluate and I’ll tell you how you teach" is very accepted. To that we can add, and with what technology? When it is proposed that learning experiences have served to think and reflect on what we learn, learn about ourselves, self-regulate our learning ... Technologies have many functions and possibilities to improve these processes of diagnostic assessment, summative and formative, customize teaching, communicating and reflecting on what has been learned, making feedback more interactive and instantaneous, more motivating activities, easier and faster to manage evaluation data, essential in e-learning, b-learning and m-learning models. At the same time, these digital resources may have problems that we must also attend to. In summary, technologies are essential resources for the evaluation of learning. These are questions from this work: What technologies can we develop a formative assessment with? What emerging technologies are there to assessment?
Keywords: Enseñanza - Innovaciones; Tecnología educativa; Assessment; Formative assessment; Information and communication technology